Production Layout Optimization Using SLP for Material Handling Cost Efficiency - taufik, Muhammad Irham; Umrah, Deva; Djayadiningrat, Dimas (Sainteks: Jurnal Sain dan Teknik, 2025)
The efficiency of facility layout plays a crucial role in determining material handling costs (OMH) within a production system. This study was conducted at PT AR Jaya, a tofu manufacturing plant in Tasikmalaya, which experienced excessive OMH due to inefficient layout and long material transfer distances between workstations. The objective of this research is to redesign the production facility layout to reduce OMH and improve workflow efficiency. A descriptive quantitative approach was employed, including field observation, primary data collection, and process mapping using Operation Process Chart (OPC), Multi Product Process Chart (MPPC), and From-To Chart. The redesign process adopted the Systematic Layout Planning (SLP) method, supported by Activity Relationship Chart (ARC) to analyze inter-process proximity. The findings reveal that the initial layout resulted in a total material transfer distance of 537.5 meters with a daily OMH of Rp60,000. The proposed layout reduced the transfer distance to 424.5 meters and OMH to Rp47,374 per day, achieving a cost efficiency of 12%. It can be concluded that a systematic facility layout redesign significantly reduces material handling costs and enhances production efficiency. It is recommended that the proposed layout be implemented and reviewed periodically to ensure long-term operational improvements.